MODELLING THE AIDS EPIDEMIC IN MALAYSIA - Ong Hong Choon (Proceedings of ICMSA, 2005)
There are generally three methods of modelling the acquired immunodeficiency syndrome (AIDS) epidemic. At one extreme is the attempt tofit a function of calendar time such as a polynomial or othermathematically convenient curves to the AIDS incidence curve while theother extreme attempts to model the full dynamics of the transmission ofthe epidemic in the population providing much insight, into thequalitative evolution of the epidemic and identifying the key variablesthat determine the future number of cases.The method of backcalculation which is intermediate between the firsttwo methods, estimates the past HIV infection rate from the AIDSincidence data and an estimate ofthe incubation period distribution. Thismethod is used on the Malaysian data to model the AIDS epidemicbecause it makes use of the Malaysian AIDS incidence which is fairlyreliable and is more reflective of the trend of the epidemic as comparedto the HIV infection rate recorded. An application is made in this studyon the AIDS incidence data in Malaysia released by the Ministry ofHealth, Malaysia using a backcalculation program and an approximateincubation period distribution to generate the current HIV infection ratefor Malaysia.Keywords: Backcalculation, AIDS modeling, HIV infection